Efficacy of oral antiparasitics in the treatment and control of gastrointestinal nematodes in horses - Oliva Santillan, Mirta (2021)
The objective of the study was to determine the efficacy of two oral antiparasitics in the control of gastrointestinal nematodes in horses. 45 mares from 2 to 4 years old were randomly distributed into three groups: I: control group, II: antiparasitic treatment. doramectin in doses of 11.4 mg / kg of body weight and III: treatment with antiparasitic fenbendazole in doses of 7.5 mg / kg of body weight, with 15 repetitions each. Stool samples were collected prior to dosing and 30 days after treatment. The fecal samples were analyzed using the modified Baermann cup technique, Kato-Katz and the Graham test. Pre and post treatment data were analyzed with parametric and non-parametric tests. The efficacy of the treatments was determined by the method of percentage reduction of eggs per gram of feces (hpg). All mares were positive for nematodes, identifying Strongylus sp, Parascaris sp and Oxyuris sp. The efficacy of doramectin was 97% and fenbendazole 51% (p <0.05).